İdari yargının görev alanında kabahatler kanunu ile meydana gelen değişiklikler - Kayabaşı, Sadi (My University, 2010)
İDARİ YARGININ GÖREV ALANINDA KABAHATLER KANUNU İLE MEYDANA GELEN DEĞİŞİKLİKLER ZET 5326 sayılı Kabahatler Kanunu ile idari yargının görev alanında meydana gelen değişikliklerin anlatıldığı tezde, öncelikle yargılama usulünde görev kavramı üzerinde durularak idari yargının görev alanı ayrıntılı şekilde anlatılmaya çalışılmıştır.Kabahatler Kanunu ile özellikle idari para cezaları konusunda değişen görevli yargı yerleri anlatılmış, bu anlamda idari yargının görev alanında meydana gelen değişikliklere değinilmiştir. Kabahatler Kanunu'nun göreve ilişkin hükümleri detaylı olarak incelenmiş, 5560 sayılı Kanun ile yapılan değişiklikten önce ve sonra olmak üzere görevli yargı yerlerinden bahsedilerek, 5728 sayılı Kanun ile idari yargının görev alanından çıkarılan düzenlemelere yer verilmiş, Kanunda yer alan ve görevli yargı yerine ilişkin olan Geçici 2, Geçici 3 ve Ek 1. maddeden söz edilerek Kabahatler Kanunu'nun yürürlüğe girmesi sonucu idari yaptırımlar konusunda idari yargının görev alanında meydana gelen değişiklikler ele alınmıştır.Bu inceleme yapılırken başta Anayasa Mahkemesi ve Uyuşmazlık Mahkemesi olmak üzere yüksek mahkeme kararlarına yer verilerek Kabahatler Kanunu sonrasında görevli yargı yeri konusunda değişikliklerin meydana geldiği üç yıllık süreç özetlenmeye çalışılmıştır. CHANGES OCCURRING IN THE SPHERE OFDUTIES IN ADMINISTRATIVE JUSTICEWITH THE MISDEMEANOR LAW MASTER’S DEGREE THESIS - ABSTRACTIn the thesis explaining changes that have occurred in the sphere of duties of administrative justice with the introduction of Misdemeanor Law 5326, an attempt was made at detailed explanation of the sphere of duties of administrative justice by focusing on the concept of duties in the trial procedure. In particular, the assigned trial locations that have changed with the Misdemeanor Law concerning administrative fines and penalties have been explained and changes have been mentioned that have occurred in this regard in the sphere of duties of the administrative justice. Provisions of the Misdemeanor Law concerning duties have been examined in details and elaborating on the proper places of trial before the after the amendment made with the introduction of the Law 5560, regulations that have been excluded from the sphere of duties of administrative justice with the Law 5728 have been indicated. Further, explaining Temporary articles 2 and 3 and Additional Article 1 of the Law that refer to the assigned location of trial, changes that have occurred in the sphere of duties of administrative justice concerning administrative sanctions as a result of the introduction of the Misdemeanor Law have been elaborated on. In the conduction of this review, decisions of high courts, primarily the Constitutional Court and Court of Jurisdictional Disputes have been cited and an attempt has been made at summarizing the three-year process during which the changes have occurred in assigned trial locations after the introduction of the Misdemeanor Law. SAD© KAYABAªI – RESUMEBorn in 1980 in the county of Devrek, province of Zonguldak, Sadi Kayabaº¹ finished elementary school at the place of his birth and graduated from middle and high schools in the province of Karabük. Upon completing in 2001 his law studies at the Faculty of Law of Istanbul University, which he started in 1997, he practiced for a while as a self-employed lawyer. Starting the career of a judge upon passing in 2004 the examination held by the Ministry of Justice, Kayabaº¹ was assigned on July 1, 2006 to his current position of a member of the Administrative Court of Bursa upon the completion of his two-year internship period.
Keywords: Hukuk; Kabahatlar Kanunu; Kamu Hukuku